Language Proficiency and Earnings of Non-Official Language Mother Tongue Immigrants: The Case of Toronto, Montreal and Quebec City - Song, Yinghua (Université d'Ottawa | University of Ottawa, 2012)
This study uses data from the 2006 Canadian Census on non-official language mother tongue immigrants over a wide range of birthplaces to examine the determinants of official language proficiency and earnings in Toronto, Montreal and Quebec City. The definition of language proficiency is based on the reported knowledge of the two official languages. The focus is on English language proficiency in Toronto and on both English and French language proficiency in Montreal and Quebec City. The results suggest that language proficiency is improved with education attainment, duration of residence, but that it is negatively correlated with age at immigration and minority language concentration. They also indicate that being bilingual in the Canadian official languages is very important for the immigrants who live in Montreal and Quebec City, while it is not necessary for those living in Toronto.